Breath Malodour - A Review - Shruti Tandon; Vishnudas Bhandari; I R D'Silva (Wolters Kluwer Medknow Publications, 2004)
The term 'Halitosis', 'Foetor oris' and 'foetor ex ore' are used to describe offensive breath. This embarrassing condition causes social, emotional and psychological anxiety. This article provides an insight into etiology, diagnosis and management of oral malodour.